2019
DOI: 10.1016/j.omtn.2019.09.030
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Anti-miR-214 Prevents Collapse of the Femoral Head in Osteonecrosis by Regulating Osteoblast and Osteoclast Activities

Abstract: Osteonecrosis of the femoral head, an intractable but common disease that eventually triggers collapse of the femoral head, is characterized by increased osteoclast activity and markedly decreased osteoblast activity in the necrotic region of the femoral head. MicroRNA (miRNA)-214 (miR-214) may play important roles in vertebrate skeletal development by inhibiting osteoblast function by targeting activating transcription factor 4 (ATF4) and promoting osteoclast function via phosphatase and tensin homolog (PTEN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…ONFH, as one of common and intractable diseases, results in the collapse of the femoral head ultimately, accompanied by the decrease of osteoblast activity in the region of ONFH. 21 EVs derived from BMSCs were found to regulate steroid-induced osteonecrosis of the femoral head. 22 Additionally, miRs are involved in various bone diseases and play a role in the mechanism of ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…ONFH, as one of common and intractable diseases, results in the collapse of the femoral head ultimately, accompanied by the decrease of osteoblast activity in the region of ONFH. 21 EVs derived from BMSCs were found to regulate steroid-induced osteonecrosis of the femoral head. 22 Additionally, miRs are involved in various bone diseases and play a role in the mechanism of ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal bone metabolism is one theory for the pathogenesis of GIONFH. Previous studies have usually focused on either osteoclasts or osteoblasts since these cells are regulated through different signalling pathways 10,22‐24 . Our study is the first to assess the effect of concurrent osteoclast and osteoblast differentiation on GIONFH through the expression of PRIP protein.…”
Section: Discussionmentioning
confidence: 93%
“…It is worth mentioning that miR-214 may serve as a potential target for small-molecule drug delivery systems. 32 Wang et al 33 have demonstrated that the function of osteoblast activity promotion was achieved by knockdown of miR-214 by adenoviral vectors in an osteonecrosis rat model. A parallel result was obtained by sponging miR-214 through baculovirus vector, and a combination of Bone Morphogenetic Protein 2 could promote the healing effect of bone synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…34 The dual-regulatory function, including inhibiting osteoblast activity and enhancing osteoclast activity, of miR-214 may play an important role in regulating osteogenesis activities. 10,12,33 In addition, targeted materials loading with miR-214 may also have profound prospects. Sun et al 35 have designed polyurethane nanomicelles modified by osteoblast-targeting peptides as delivery systems to deliver antagomiR-214 to osteoblasts, which was proved to be successful in an ovariectomized osteoporosis mouse model, since bone mass and formation were improved significantly.…”
Section: Discussionmentioning
confidence: 99%